1994
DOI: 10.1002/j.1460-2075.1994.tb06548.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of JAK protein tyrosine kinases as signaling molecules for prolactin. Functional analysis of prolactin receptor and prolactin-erythropoietin receptor chimera expressed in lymphoid cells.

Abstract: The mechanism of action of prolactin (PRL) was studied in murine lymphoid BAF‐3 cells transfected with either the long form of the PRL receptor (PRL‐R), or a chimeric receptor consisting of the extracellular domain of the PRL‐R and the transmembrane and intracellular domain of the erythropoietin receptor (PRL/EPO‐R). PRL sustained normal and long‐term proliferation of BAF‐3 cells expressing either the PRL‐R or the hybrid PRL/EPO‐R. Upon [125I]PRL cross‐linking, both types of BAF‐3 transfectants were shown to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
1

Year Published

1994
1994
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(82 citation statements)
references
References 45 publications
(23 reference statements)
3
77
1
1
Order By: Relevance
“…The prolactin receptor activates Jak 2 in vivo [29][30][31][32]. GM-CSF and IFN-y receptors are both capable of activating Jak2 [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The prolactin receptor activates Jak 2 in vivo [29][30][31][32]. GM-CSF and IFN-y receptors are both capable of activating Jak2 [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Also, JAK2 and TYK2 are activated upon IL-12 stimulation and are proposed to play a critical role in IL-12 mediated T-cell di erentiation (Bacon et al, 1995). Similarly, JAK kinases have been shown to play a key role in the signal transduction pathways initiated in response to stimulation by growth hormone (Argetsinger et al, 1993), prolactin Dusanter-Fourt et al, 1994) and G-CSF (Nicholson et al, 1994;Shimoda et al, 1994). The interferons also transduce their signals via the JAK kinases, JAK1, JAK2 and TYK2 Velazquez et al, 1992Velazquez et al, , 1995Watling et al, 1993).…”
Section: Activation Of Jak Kinases By Cytokines/interferons and Growtmentioning
confidence: 99%
“…8,25 The hGMR and these receptors activate signaling molecules similar to EPOR, such as Janus kinase 2 and signal transducer and activator of transcription 5. [33][34][35][36][37] Therefore, cytokine receptors, which activate a set of downstream signaling molecules similar to those activated by EPOR, may be able to substitute for EPOR. On the other hand, Wessely et al 38 analyzed the effect of hGMR signal on erythropoiesis using avian hematopoietic progenitors and found that hGMR only partially substituted for the activities of EPOR.…”
Section: Erythropoiesis In Mice Having Hgm-csfr But No Epor 3623mentioning
confidence: 99%